1999
DOI: 10.1590/s0100-879x1999001200009
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the action of nitric oxide in human septic shock increases systemic vascular resistance and has detrimental effects on pulmonary function after a short infusion of methylene blue

Abstract: To investigate the role of nitric oxide in human sepsis, ten patients with severe septic shock requiring vasoactive drug therapy and mechanical ventilation were enrolled in a prospective, open, non-randomized clinical trial to study the acute effects of methylene blue, an inhibitor of guanylate cyclase. Hemodynamic and metabolic variables were measured before and 20, 40, 60, and 120 min after the start of a 1-h intravenous infusion of 4 mg/kg of methylene blue. Methylene blue administration caused a progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 48 publications
2
50
0
2
Order By: Relevance
“…The dosing used for refractory septic shock has included a single bolus, repeated bolus based on response, low-dose infusion, and infusions followed by a bolus. It is clear based on other studies that the use of high doses of methylene blue, typically doses greater than 7 mg/kg, is associated with adverse effects such as paradoxical induction of methemoglobinemia, acute hemolytic anemia, and detrimental effects on pulmonary function [86,87].…”
Section: The No-cgmp Pathway In Anaphylaxis and The Role Of Methylenementioning
confidence: 99%
“…The dosing used for refractory septic shock has included a single bolus, repeated bolus based on response, low-dose infusion, and infusions followed by a bolus. It is clear based on other studies that the use of high doses of methylene blue, typically doses greater than 7 mg/kg, is associated with adverse effects such as paradoxical induction of methemoglobinemia, acute hemolytic anemia, and detrimental effects on pulmonary function [86,87].…”
Section: The No-cgmp Pathway In Anaphylaxis and The Role Of Methylenementioning
confidence: 99%
“…In this case, we report the need for a prolonged infusion of MB over a period of 120 hr in a patient with intractable septic shock. Previous research has demonstrated that MB may be efficacious in septic shock when given by intravenous bolus or short-term (B6 h) infusions, 3,4,9,11,[16][17][18] although a case report of a longer-term infusion of 44 hr has been described. 12 Despite standard treatment for septic shock with early goal-directed therapy, conventional vasopressors, including norepinephrine, epinephrine, and vasopressin, our patient responded only to the administration of MB.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,16,23 In patients with septic shock, bolus doses of MB have been associated with increases in pulmonary vascular resistance, 5 and caution has been advised in patients with acute respiratory distress syndrome. 18 Additionally, while little is known about the appropriate dose of MB, a recent study demonstrated that bolus doses of 7 mgÁkg -1 may compromise splanchnic perfusion, while maintaining dosedependent hemodynamic properties. 24 In addition, the safety of MB for patients undergoing CRRT has not been adequately studied.…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue has been used in several studies in human sepsis (Schneider et al, 1992;Daemen-Gubbels et al, 1995;Gachot et al, 1995;Preiser et al, 1995;Andresen et al, 1998;Weingartner et al, 1999;Donati et al, 2002). MB was effective in increasing MAP of septic rats only when injected 48 h after the CLP procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Several uncontrolled studies in patients with septic shock requiring adrenergic support have shown that sGC inhibited by MB restores the mean arterial pressure and improves the myocardial contractility (Schneider et al, 1992;Daemen-Gubbels et al, 1995;Preiser et al, 1995;Andresen et al, 1998). On the other hand, sGC inhibition was found to be deleterious to gas exchange in the lung and myocardial contractility (Gachot et al, 1995;Weingartner et al, 1999). These findings prompted some researchers to question the use of MB in human sepsis (Schneider, 1995), whereas other groups found that the beneficial effects are worth the risk (Donati and Preiser, 2006).…”
mentioning
confidence: 99%